(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
Primary schools in Nigeria are facing a lot of challenges regarding management over the years. However, headteachers are charged with the responsibility of overseeing and managing the affairs of their respective primary schools. Based on this the paper is titled Qualitative Study on management of Primary School level of Education in Nigeria: Problems and Prospects .Therefore, concept and objectives of primary education, concept of management were highlighted. Management of Primary Education in Nigerian Primary Schools, ways by which primary schools are managed such as; management of human resources, school records, school facilities, school financial resources and primary school curriculum. Challenges facing management of primary education were also explained and these are; inadequate funding, head teachers’ factor, lack of cooperation by the teachers, inadequate facilities, politically motivated appointment. The paper recommended among the following’ Government should ensure fairness and impartiality in the appointment of primary school teachers, Sustainable and adequate funding of primary schools should be provided by stakeholders and headteachers should discharge their duties with integrity and fairness, treating all subordinates equally.